2022
DOI: 10.1093/ajhp/zxac043
|View full text |Cite
|
Sign up to set email alerts
|

Decreased isavuconazole trough concentrations in the treatment of invasive aspergillosis in an adult patient receiving extracorporeal membrane oxygenation support

Abstract: Purpose We present the case of a 56-year-old man with stage IV sarcoidosis on veno-venous extracorporeal membrane oxygenation (VV-ECMO) support for the management of respiratory failure receiving treatment with isavuconazole for invasive aspergillosis. Summary VV-ECMO is an increasingly utilized life support therapy for patients with cardiac and/or respiratory failure, but its impact on medication dosing is poorly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
5
7
0
Order By: Relevance
“…In contrast, the isavuconazole C min in cases C and D did not exceed the target of 1 mg/L when correcting for the standard maintenance dose of 200 mg q24h. The latter results are in line with the previous reports by Zhao et al [ 3 ] and Miller et al [ 1 ], in which subtherapeutic exposure following a standard dosing regimen was documented and ascribed to ECMO as such .…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, the isavuconazole C min in cases C and D did not exceed the target of 1 mg/L when correcting for the standard maintenance dose of 200 mg q24h. The latter results are in line with the previous reports by Zhao et al [ 3 ] and Miller et al [ 1 ], in which subtherapeutic exposure following a standard dosing regimen was documented and ascribed to ECMO as such .…”
supporting
confidence: 93%
“…Unfortunately, based on the previously published reports [ 1 3 ] and our case series, the independent impact of ECMO on isavuconazole exposure in critically ill patients cannot be assessed. Therefore, the key question whether subtherapeutic isavuconazole exposure in ECMO patients is caused by ECMO or by critical illness itself remains unanswered.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The nine ECMO patients included in our study exhibited lower isavuconazole drug levels, which is in line with other reports, 16,28–30 in which a sum of nine ECMO patients had been included. In contrast, one study reported sufficient levels of this drug in seven ECMO patients with prophylactic administration 31 .…”
Section: Discussionsupporting
confidence: 91%
“…In another case of a patient with pulmonary blastomycosis, for which therapeutic target concentration of isavuconazole was set at 3 mg/L, these concentrations could be only achieved by increasing the dose of isavuconazole (200 mg bid), while the standard dose resulted in a concentration of 1.9 mg/L [ 85 ]. In an additional case of a patient treated with ECMO but no RRT, treatment with voriconazole did not result in adequate plasma levels, while standard dose of isavuconazole resulted in initial adequate plasma level (1.7 mg/L), which nevertheless decreased to 0.7 mg/L over the following 12 days [ 86 ]. The ECMO circuit exchange (which was done approximately every 7 days) was cited as the most probable cause of the decrease in plasma levels.…”
Section: The Impact Of Renal Replacement Therapy Hemodialysis and Ecm...mentioning
confidence: 99%